Megastigmus seed wasp damage on native Schinus terebinthifolia drupes in ecological restoration area in Brazil - Ghiotto, Thais Carneiro; Nascimento Prado, Marcelle Cristine do; Fischer Giuliani, Graziella Kurpjuweit; Tavares, Wagner de Souza; Masson, Marcus Vinicius; Guerreiro, Julio Cesar; Prado, Evandro Pereira [UNESP]; Carvalho, Amelia Guimaraes; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola; Ferreira-Filho, Pedro Jose (Nature Publishing Group, 2019)
Megastigmus transvaalensis Hussey (Hymenoptera: Torymidae) parasitizes drupes of Rhus genus plants in Africa and Schinus (Anacardiaceae) in South America. This exotic wasp damages Schinus terebinthifolia Raddi drupes in native forests and ecological restoration areas in Brazil. The objective of the present study was to investigate the precipitation, temperature and relative humidity effects on M. transvaalensis flight activity, and to determine the parasitism rate and sex ratio of this wasp on S. terebinthifolia plants. The study was conducted with yellow sticky traps and S. terebinthifolia drupes collected in an ecological restoration area, from August 2014 to September 2015, in the Sorocaba municipality, Sao Paulo state, Brazil. Megastigmus transvaalensis populations were negatively correlated with maximum and minimum temperatures and precipitation, with population peaks at the end of May 2015, with 927 insects per evaluation (48.8 adults per trap). The M. transvaalensis sex ratio was higher in the laboratory (0.42) than in the field (0.08). The parasitism rate of S. terebinthifolia drupes by M. transvaalensis ranged from zero to 36.3% under natural environmental conditions. Megastigmus transvaalensis can be monitored with yellow sticky traps. Damage by M. transvaalensis in S. terebinthifolia drupes may decrease the germination of the seeds and the establishment of this plant in native and restoration ecological areas.